Determining bond strength of seven-wire strands in prestressed concrete. (October 2021) - Mohandoss, Prabha; Pillai, Radhakrishna G.; Gettu, Ravindra
Highlights: Challenges with the existing bond test methods for PTC system and need for a new test procedure are explained. A conceptual model on strand-concrete bond behavior and a rational test method to determine τ b as the stress corresponding to the yield bond stress (τ yield ) are proposed. Proposed test method determines the bond strength as a strand-concrete interface property, independent of prestress level and embedment length. The failure of strand-concrete depends on the failure of concrete keys. Abstract: The three mechanisms governing the strand-concrete (S-C) bond in pretensioned concrete (PTC) systems are: (i) adhesion, (ii) mechanical interlock, and (iii) friction. These mechanisms can be influenced by various parameters like the compressive strength of concrete ( fc ), applied prestress ( fps ), and embedment length of the strand ( le ). The existing test methods for S-C systems use unstressed strands and defines bond strength (τ b ), as the stress corresponding to a slip of 2.5 mm at free end (say, τ 2.5 ). The unstressed strands and τ 2.5 approach may lead to unconservative results and significant scatter. This paper presents the experimental program on the effects of fc (43 and 62 MPa), fps (0.1 fpu and 0.7 fpu ), and le (500 and 1000 mm) on the bond stress-slip (τ- s ) behaviour in PTC systems. Analysis of the results of tests on 24 specimens indicated that (i) defining the τ b as τ 2.5 at the free end is not suitable for PTC specimens and (ii) the τ 2.5 at live end exhibits significant scatter and is dependent on the embedment length, le . Consequently, the paper proposes a conceptual model on strand-concrete bond behavior and a rational method to determine τ b as the stress corresponding to the yield bond stress (τ yield ). The determined τ yield is independent of fps and le and exhibits less scatter than τ 2.5 . Finally, the use of taut strand specimens is recommended as they are easier to prepare than stressed strand specimens, to determine τ yield .